Phosphodiesterase III inhibitor promotes drainage of cerebrovascular β‐amyloid. (8th July 2014) - Maki, Takakuni; Okamoto, Yoko; Carare, Roxana O.; Hase, Yoshiki; Hattori, Yorito; Hawkes, Cheryl A.; Saito, Satoshi; Yamamoto, Yumi; Terasaki, Yasukazu; Ishibashi‐Ueda, Hatsue; Taguchi, Akihiko; Takahashi, Ryosuke; et al.
Abstract Objective Brain amyloidosis is a key feature of Alzheimer's disease (AD). It also incorporates cerebrovascular amyloid β (Aβ) in the form of cerebral amyloid angiopathy (CAA) involving neurovascular dysfunction. We have recently shown by retrospective analysis that patients with mild cognitive impairment receiving a vasoactive drug cilostazol, a selective inhibitor of phosphodiesterase (PDE) III, exhibit significantly reduced cognitive decline. Here, we tested whether cilostazol protects against the disruption of the neurovascular unit and facilitates the arterial pulsation‐driven perivascular drainage of Aβ in AD/CAA. Methods We explored the expression of PDE III in postmortem human brain tissue followed by a series of experiments examining the effects of cilostazol on Aβ metabolism in transgenic mice (Tg‐SwDI mice) as a model of cerebrovascular β‐amyloidosis, as well as cultured neurons. Results We established that PDE III is abnormally upregulated in cerebral blood vessels of AD and CAA subjects and closely correlates with vascular amyloid burden. Furthermore, we demonstrated that cilostazol treatment maintained cerebral hyperemic and vasodilative responses to hypercapnia and acetylcholine, suppressed degeneration of pericytes and vascular smooth muscle cells, promoted perivascular drainage of soluble fluorescent Aβ1‐40, and rescued cognitive deficits in Tg‐SwDI mice. Although cilostazol decreased endogenous Aβ production in cultured neurons, C‐terminal fragment of amyloid precursor protein expression was not altered in cilostazol‐treated Tg‐SwDI mice. Interpretation The predominant action of cilostazol on Aβ metabolism is likely to facilitate Aβ clearance due to the sustained cerebrovascular function in vivo. Our findings mechanistically demonstrate that cilostazol is a promising therapeutic approach for AD and CAA.